Evaluating Changes in del Nido Cardioplegia Practices in Adult Cardiac Surgery - Likosky, Donald S. (J Extra Corpor Technol, 2020)
There has been a rapid adoption of the use of del Nido cardioplegia (DC) among adults undergoing cardiac surgery. We leveraged a multicenter database to evaluate differences over time in the choice and impact of cardioplegia type (DC vs. blood) among patients undergoing cardiac surgery. We evaluated 26,373 patients undergoing non-emergent coronary artery bypass and/or valve surgery between 2014–2015 (early period) and 2017–2018 (late period) at 31 centers. DC was compared with blood-based cardioplegia (BC: 1:1, 2:1, 4:1, 8:1, and variable ratio). We evaluated whether treatment choice differed across prespecified patient characteristics, procedure type, and perfusion practices by time period. We evaluated increased DC use with clinical outcomes (major morbidity and mortality, prolonged intubation, and renal failure), after adjusting for baseline characteristics, procedure type, center, and year. DC use increased from 19.6% in 2014–2015 to 41.5% in 2017–2018, p < .001. Increased DC use occurred among coronary artery bypass grafting (CABG), valve, and CABG + valve procedures, all p < .001. Differences in median procedural duration increased over time (DC vs. BC): 1) bypass duration was 11.0 minutes shorter with DC in the early period and 27.0 minutes shorter in the late period, and 2) cross-clamp duration was 7.0 minutes shorter with DC in the early period and 17.0 minutes shorter in the late period, all p < .001. There were no statistical differences in adjusted odds of major morbidity and mortality (odds ratio [OR](adj): 1.01), prolonged intubation (OR(adj): .99), or renal failure (OR(adj): .80) by DC use (p > .05). In this large multicenter experience, DC use increased over time and was associated with reduced bypass and ischemic time absent any significant differences in adjusted outcomes.